2022
DOI: 10.3390/ijms231911464
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Biological Alterations after Photon, Proton, and Carbon Ions Irradiation in Human Chondrosarcoma Cells Linked with High-Quality Physics Data

Abstract: Chondrosarcomas are particularly difficult to treat due to their resistance to chemotherapy and radiotherapy. However, particle therapy can enhance local control and patient survival rates. To improve our understanding of the basic cellular radiation response, as a function of dose and linear energy transfer (LET), we developed a novel water phantom-based setup for cell culture experiments and characterized it dosimetrically. In a direct comparison, human chondrosarcoma cell lines were analyzed with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…CDKN2A (p16) and CDKN1A (p21), were significantly increased in CAFs after IR (Figure 2B). [39,40] The mRNA expression levels of TGF-𝛽, IL-6, and IL-10 were also determined. Compared with CAFs, SC CAFs showed markedly increased expression of SASPs (Figure 3C).…”
Section: Clearance Of Sc Cafs By Fap-car-cm@plga-ab Npsmentioning
confidence: 99%
“…CDKN2A (p16) and CDKN1A (p21), were significantly increased in CAFs after IR (Figure 2B). [39,40] The mRNA expression levels of TGF-𝛽, IL-6, and IL-10 were also determined. Compared with CAFs, SC CAFs showed markedly increased expression of SASPs (Figure 3C).…”
Section: Clearance Of Sc Cafs By Fap-car-cm@plga-ab Npsmentioning
confidence: 99%
“…In the particular case of chondrosarcoma, in vitro studies showed a higher efficiency of carbon ions on multiple chondrosarcoma cell lines [ 10 , 82 , 101 , 102 ]. The cellular effect was directly connected with the LET of carbon ions, inducing a prolonged block of irradiated cells in the G2 phase of the cell cycle and longer-lasting unrepaired cell damage [ 101 , 103 ]. Carbon ion radiations generated a positive regulation of several DNA repair genes (ATM, NBN, ATXR, XPC, XRCC1/2/3, ERCC1, XPC, and PCNA), activating a large range of DNA repair mechanisms [ 103 ].…”
Section: Hadrontherapy and Combined Therapy Of Chondrosarcomamentioning
confidence: 99%